Mesothelioma Heterogeneity: Potential Mechanisms - Emanuela Felley-Bosco (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Mesothelioma is a rare aggressive cancer that develops from the mesothelium. Recent molecular analyses have defined four different types of mesothelioma based on gene expression and two major molecularly-defined groups based on prognosis. In this volume, potential mechanisms causing this heterogeneity are explored. The different chapters include heterogeneity learned from experimental animal models in NF2/Hippo pathway signaling, stem cell signaling pathways, the tumor microenvironment, and micro RNA secretome. Novel aspects deserving attention such as the implication of long, non-coding RNA in disease heterogeneity are described. The volume also includes the description of tools useful to address some specific questions such as an assessment of the copy number variations of two tumor suppressors frequently mutated in mesothelioma or an investigation of Macrophage Inhibition Factor signaling in mesothelioma.